Strategi Pemasaran Komunitas And Implikasinya Pada Loyalitas Merek Toyota Di Indonesia [Community Marketing Strategy and Its Implication on Brand Loyalty Toyota in Indonesia] - Aditya Wardhana (DeReMa (Development Research of Management): Jurnal Manajemen, 2016)
This research study examined the strategic community marketing and its impact on brand loyalty of Toyota in Indonesia. Elements of the strategic community marketing were: (a) critical awareness and reflection, (b) building community identity, political and legislative actions, (c) culturally relevant practice, (d) spontaneous associations of neighbors, colleagues, or groups with a particular interest in a topic, (e) leadership in communities; (f) empowerment; and (g) critical reflection. Elements of the brand loyalty were: perceived risk, inertia, habit, involvement, satisfaction, and relationship between product or service providers. The population of this study was 4,000 customers from 29 Toyota communities in Indonesia who used Toyota cars. The size of the sample was 400 respondents. The sampling method used nonprobability sampling by incidental sampling. The results by using structural equation modeling (SEM) found significant impacts of strategic marketing community on brand loyalty of Toyota in Indonesia.